2017
DOI: 10.1080/14719037.2017.1383784
|View full text |Cite
|
Sign up to set email alerts
|

An organizational culture for all seasons? How cultural type dominance and strength influence different performance goals

Abstract: The New Public Management wave pressured the management of services mainly toward structural changes to improve performances. However, organizational culture might influence results, especially in settings characterized by strong professional control and political influence on decision-making.This study tests how organizational culture influences performances and investigates whether a specific culture type is most effective in fostering organizational results in a universal and tax-based health system where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
1
32
0
2
Order By: Relevance
“…Tseng (2010) reported significant positive influence of adhocracy and hierarchical cultures on performance. Similar results were obtained by Calciolari, Prenestini, and Lega (2018). However, Fekete and Bocskei (2011) established that clan and adhocracy cultures were significant positive predictors of performance.…”
Section: Organizational Culture and Performancesupporting
confidence: 64%
“…Tseng (2010) reported significant positive influence of adhocracy and hierarchical cultures on performance. Similar results were obtained by Calciolari, Prenestini, and Lega (2018). However, Fekete and Bocskei (2011) established that clan and adhocracy cultures were significant positive predictors of performance.…”
Section: Organizational Culture and Performancesupporting
confidence: 64%
“…Their findings show that of the four CVF culture types, the clan culture correlates best with a high level of BPM adoption. However, the hierarchy culture, which can be assumed to be dominant in public administration (Calciolari et al 2018;Cameron and Quinn 2011;Grau and Moormann 2014), was found to be connected to the lowest level of BPM adoption. The study of Indihar Š temberger et al (2018) followed a similar approach and also applied the CVF to analyze the relationship between different organizational culture types, introduction strategies and BPM adoption success.…”
Section: Business Process Management Culturementioning
confidence: 96%
“…Therefore, in the context of the Spanish public organizations, HD results are crucial to take into consideration as long as it is associated with the success of TBW since HD influences interpersonal relationships among the members of the team (Stewart & Barrick, 2000) and the employee’s commitment (Geary & Dobbins, 2001; Wood & Menezes, 1998). According to contextual theory (Lepak, Bartol & Erhardt, 2005; Oc, 2018; Osborn, Hunt & Jauch, 2002) (the main theory of this study 1 ), HD might drastically influence the degree of participation and consensus of public employees in their departments and/or work teams, characterized by active professional and administrative control (Calciolari, Prenestini & Lega, 2018) (i.e., bureaucracy). Thus, in organizations marked by considerable distances of power (very vertical organizations), major hierarchical differences are assumed since they characterize the prevailing inequality.…”
Section: Introductionmentioning
confidence: 98%